The impact of external pressure and sustainable management practices on manufacturing performance and environmental outcomes. Issue 9 (5th September 2016) - Adebanjo, Dotun; Teh, Pei-Lee; Ahmed, Pervaiz K.
Abstract : Purpose: The purpose of this paper is to investigate the direct effect of external pressure on environmental outcomes and manufacturing performance and examine the mediating effect of sustainable management practice. Design/methodology/approach: This study draws upon institutional theory and resource-based view to understand how factors such as external pressure and sustainable management relate with environmental outcomes and manufacturing performance. The model specifies previously unexplored direct and mediating relationships between external pressure, sustainable management, environmental outcomes and manufacturing performance. The empirical analysis is based on data collected from the sixth edition of the International Manufacturing Strategy Survey. The research hypotheses are tested using structural equation modelling. Findings: Results show that while there is a significant direct and mediating relationship between external pressure, adoption of formal sustainability programmes and environmental outcomes, such significant relationships do not exist with manufacturing performance. Practical implications: The study shows that external pressure can influence adoption of sustainable practices but this does not necessarily lead to an improvement in manufacturing performance. As such managers need to identify the actual benefits of sustainability and weigh them up against costs of implementing such programmes. Originality/value: The relationship between the adoption of sustainable practices and organisational performance is a complex one. In contrast to previous studies, this study found that while external pressure and sustainable management relate positively with environmental outcomes, no such relationship exists with manufacturing performance. This raises a number of question marks over naive implementation of sustainable strategies.